Differential Evolution Algorithm Based Very Fast Renewable Energy System Optimisation Tool Design - Altin, Cemil (Elektronika ir Elektrotechnika, 2023)
In this study, an optimisation tool that uses the differential evolution algorithm with a special distribution strategy is designed for the first time to be used in the optimisation of hybrid renewable energy systems. The developed tool and the hybrid optimisation model for multiple energy resources (HOMER) optimisation programme were compared. The tool is much faster than the HOMER programme and can produce almost the same results as HOMER. In addition, a heuristic-based optimisation technique was used for the first time to generate extremely comprehensive findings. The capacity shortage parameter, which is not used much in the literature, is used as a reliability parameter. The cost of energy (COE) was used as the cost function. The results are promising for detailed optimisation studies in this area.